The Lulennial II : A Low-Hanging Fruit - Berardini, Andrew; Lulu, Mexico City; Sharp, Chris; Jauregui, Gabriela ([S.l.] : Mousse Publishing, 2018)
Agematsu, Yuji ; Akashi, Kelly ; Akay, Derya ; Beier, Nina ; Bendaña, Luis Miguel ; Bennani, Meriem ; Brannon, Matthew ; Conlon, Donna ; Harker, Jonathan ; Geys, Jef ; Hernandez, Rodrigo ; Katz, Allison ; Lara, Adriana ; Lupo, Nancy ; Mahmoud, Nevine ; Nisenbaum, Aliza ; Ramírez-Figueroa, Naufus ; Shimabuku ; Shire, Peter ; Sierra, Gabriel ; Verzutti, Erika ; von Wulffen, Amelie ; Vukoje, Maja
The Lulennial II: A Low-Hanging Fruit, Lulu, Mexico City, 06/02 - 01/04, 2018
boek